The Early Vigilance of Dengue Hemorrhagic Fever Outbreak in the Community (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Early Awareness of Extraordinary Events of Dengue Hemorrhagic Fever (DHF) was asked to community (n= 130). Precautions were measured based on community knowledge, attitudes, and behavior. Knowledge, attitude, and behavior are constructs (in the form of a composite variable) from an early awareness of DHF outbreak. The result showed that the knowledge related to the transmission factor and the proliferation of dengue disease was quite good (72.3%). The DHF risk control was also good (93.9%) while the dengue fever eradication was still poor (67.7%). However, the attitude showed that it is still not ready to act on the basis of consciousness. Meanwhile, the results of the data analysis identified that the model of the early awareness measurement on DHF outbreak which consisted of construct variables (knowledge, attitude, and action) were a perfect fit. Based on the measurement model, the level of community awareness on DHF disease can be measured. This showed that the level of early awareness of DHF disease was good 76.2% and only 3.8% were less alert. This means although the less alert percentage is quite small, if people have an attitude of indifference to the prevention of DHF then the impact will affect a wider community.